ANALISIS DETERMINAN YANG MEMENGARUHI CASH HOLDING - Satyapratama, Matthew; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine the impact of leverage, firm size, growth opportunity, net working capital, profitability, and capital expenditure on the company's cash holding. This study uses data from manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020 with a sample of 19 companies after the elimination of criteria. The data in this study were processed using the e-views 12 program with the EGLS panel model (cross-section random effects). The conclusion of this study shows that net working capital and profitability have a positive impact on cash holding, but leverage and capital expenditure do not have a positive influence on cash holding, while firm size and growth opportunity do not negatively affect cash holding.